PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA Al-ZENA SKIN CARE PATI CABANG WINONG) - Natalia Puji Lestari; Agus Hermani (Universitas Diponegoro, 2017)
Product and service quality are the factors that can influence the high loyalty of Al-Zena Skin Care Pati of Branch Winong’s customers. With the good quality products andgood services, it will further increase the loyalty of Al-Zena Skin Care Pati of BranchWinong customers.The purpose of this study is to determine the effects of product and service quality ofAl-Zena Skin Care Pati of Branch Winong’s customers. The type of research used isaccidental sampling and explanatory research, with samples of 100 respondents of Al-Zena Skin Care Pati of Branch Winong’s customers. The sampling technique used ispurposive sampling with the criteria of respondents aged over 15 years who have amember card and at least they are active in the last 3 months in using products and thebeauty treatment in Al-Zena Skin Care Pati of Branch Winong. Data collection usingquestionnaires with Likert measurement scale. The researcher uses many kinds of dataanalysis such as validity test, reliability test, correlation coefficient (R), and simple linearregression, coefficient of determination (R2), t test and F test by using SPSS program.The results of this study concludes that product and service quality have strong andsignificant influences on customer loyalty, either partially or simultaneously. Product andservice quality together have a positive effect on customer’s loyalty, which means productand service quality give influences to the level of customer’s loyalty. Product and servicequality have strong influences on customer’s loyalty as it is evidenced by the correlationcoefficient (R) of 0.711.